1963
DOI: 10.1063/1.1729174
|View full text |Cite
|
Sign up to set email alerts
|

Low-Temperature Properties of Evaporated Lead Films

Abstract: Lead films have been deposited onto room-temperature substrates having low thermal expansion coefficients and the residual mechanical stresses present in these films have been determined as a function of film thickness and film purity. At room temperature no measurable stress (<5×107 dyn/cm2) was present in any film. At 78° and 4.2°K the stress σ was given by σ=α+β/d, where α is a constant dependent on temperature and d is the film thickness. A model involving surface pinning of dislocations predicts an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1978
1978
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…Pb is known to suffer from high thermal stress when cooled to liquid He temperatures which manifests in the formation of crystallites going hand in hand with a thinning of the surrounding material [14,15]. This was also observed here and necessitates a metal thickness higher than the standard value of 200 nm.…”
Section: Methodsmentioning
confidence: 58%
“…Pb is known to suffer from high thermal stress when cooled to liquid He temperatures which manifests in the formation of crystallites going hand in hand with a thinning of the surrounding material [14,15]. This was also observed here and necessitates a metal thickness higher than the standard value of 200 nm.…”
Section: Methodsmentioning
confidence: 58%
“…Lahiri (1970) suggested that hillock growth may be due to grain boundary sliding and diffusion creep. Chaudhari (1974) proposed that hillock growth is a result of local stress relaxation, possibly by dislocation slip or twinning. The potential gradient resulting from differential relaxation causes a mass flow along the interface between the film and substrate.…”
Section: Hillock Formation In Thin Filmsmentioning
confidence: 99%
“…Combining the capillary and elastic contribution to the change in energy associated with forming a hole in an otherwise continuous film is given by G = nr 2 h jC' ) -2mh j 2 c.oa + nr2y s + 2mhj "I fv (13) where "Is = Y fs + "If v -Y sv ' The equilibrium island shape may be found by minimizing this equation with respect to r /hj for fixed island volume V = nr 2 hj. Performing this minimization, the equilibrium island shape is given by the solution to the following equation:…”
Section: Global Equilibriummentioning
confidence: 99%